Influence of Processing Parameters and Molecular Weight on the Morphology and Properties of High‐Performance PffBT4T‐2OD:PC71BM Organic Solar Cells. Issue 23 (28th September 2015) - Ma, Wei; Yang, Guofang; Jiang, Kui; Carpenter, Joshua H.; Wu, Yang; Meng, Xiangyi; McAfee, Terry; Zhao, Jingbo; Zhu, Chenhui; Wang, Cheng; Ade, Harald; Yan, He
Abstract : The influences of various processing parameters and polymer molecular weight on the morphology and properties of poly[(5, 6‐difluoro‐2, 1, 3‐benzothiadiazol‐4, 7‐diyl)‐alt‐(3, 3′′′‐di(2‐octyldodecyl) 2, 2′;5′, 2″;5″, 2′′′‐quaterthiophen‐5, 5′′′‐diyl)] (PffBT4T‐2OD)‐based polymer solar cells (PSCs) are investigated. High spin rate/high temperature conditions are found to significantly reduce polymer crystallinity and change polymer backbone orientation from face‐on to edge‐on. Most surprisingly, it is found that the median domain sizes of PffBT4T‐2OD:PC71BM blends processed at different temperatures/spin rates are nearly identical, while the average domain purity and the molecular orientation relative to polymer:fullerene interfaces can be significantly changed by the processing conditions. A systematic study is carried out to identify the roles of individual processing parameters including processing temperature, spin rate, concentration, and solvent mixtures. Furthermore, the effect of molecular weight on morphology control is also examined. These detailed studies provide important guidance to control and optimize various morphological parameters and thus electrical properties of PffBT4T‐2OD‐type materials for the application in PSC. Abstract : The morphology features of organic solar cells based on a high‐efficiency polymer that yields an efficiency >10% are investigated. The molecular orientation relative to the substrate and donor/acceptor interface, domain purity, and multilength scale phase separation are all sensitive to the spin‐rate and temperature in the solution. The molecular weight is critical for the temperature dependence aggregation in solution, which impacts the structure in the film.